Amniotic Fluid Embolism Treated with Veno-Arterial Extracorporeal Membrane Oxygenation - Robert Gitman; Bradlee Bachar; Byron Mendenhall (Case Reports in Critical Care)
Amniotic fluid embolism (AFE) is an extremely rare yet fatal obstetric emergency. AFE presents as sudden cardiovascular collapse after a breach of maternal-fetal membranes and is often complicated by severe coagulopathy. We present a case where an AFE was treated with veno-arterial extracorporeal membrane oxygenation (ECMO) to help overcome the acute cardiopulmonary insult. The use of echocardiography proved to be an invaluable tool to help guide treatment and optimal duration of ECMO in the face of severe coagulopathy.